"I don't want to grow up, I'm a [Gen X, Y, Me] kid": Increasing maturity fears across the decades. (November 2017) - Smith, April; Bodell, Lindsay P.; Holm-Denoma, Jill; Joiner, Thomas; Gordon, Kathryn; Perez, Marisol; Keel, Pamela
The current studies examined the hypothesis that maturity fears are increasing among undergraduate men and women from the United States over time. Study 1 used a time-lag method to assess generational effects of maturity fears among a large sample ( n = 3291) of undergraduate men and women assessed in 1982, 1992, 2002, and 2012. Results revealed that both men and women reported significantly higher rates of maturity fears across time. Study 2 replicated these findings, and used a more restricted time frame to more closely examine the rate of change. Undergraduate women ( n = 673) were assessed in 2001, 2003, 2009, and 2012. Maturity fears were again found to increase from 2001 to 2012. Recent cohorts of emerging adults seem more reluctant to mature than previous cohorts. Many contributing factors may be at play, including challenging economic times, social pressures to remain youthful, and/or internal fears of assuming increased responsibility.